Efectividad de la estimulación temprana en los hitos del desarrollo motor y sensorial en niños del Centro de Atención Integral Kraaker de Babahoyo, periodo octubre 2024-abril 2025. - Campi Goyes, Nahomi Sarah (2025)
The purpose of this project is to evaluate the effectiveness of early stimulation on the motor and sensory development of children at the Kraaker Comprehensive Care Center located in Babahoyo, during the period between October 2024 and April 2025. Early stimulation is considered a relevant strategy to enhance the physical, cognitive, social and emotional skills of children, which will allow them to achieve essential milestones in their comprehensive development. A descriptive methodological approach will be adopted, which will combine various methods, such as direct observation, and surveys aimed at caregivers and physiotherapists. The proposed interventions include sensory activities, such as massage, tactile and visual stimulation, as well as motor games designed to strengthen both fine and gross motor skills. The expected results will facilitate the identification of significant changes in motor and sensory skills after participating in the stimulation sessions. Likewise, it is anticipated that these findings will contribute to the design of more effective and personalized intervention programs, which will improve the quality of life of children and reduce inequalities in access to appropriate stimuli for their development.